Testing Of The Cream Formula Turmina Right Extract Against The Inhibition Of The Development Of Melanoma Cells - Vera, Vera Estefania Kaban; Jansen Silalahi; Sumaiyah (Publisher Cv. Inara, 2022)
Cancer is one of the biggest causes of death in the world and is still a health problem that still cannot be found the right treatment to overcome it. One of the cancers that cannot be ruled out is skin cancer, which occurs as a result of being exposed to direct sunlight for a long time and often without using skin protection or sunscreen. Cancer treatment that is currently being carried out is surgical therapy, chemotherapy which has adverse side effects for patients such as therapy that not only kills cancer cells but also healthy cells. The current therapy needed is the formulation of topical preparations that can be used to inhibit the growth of cancer cells. This study aims to make a cream preparation from turmeric extract to inhibit the growth of melanoma cells. This research was made experimentally by formulating turmeric rhizome extract into cream preparations at a concentration of 0.5%; 2.5% ; 5% ; 10% and 20% were tested against melanoma cell inhibition in vitro. Melanoma cell inhibition testing was carried out using the MTT Assay method by looking at the IC50 value of turmeric extract cream in inhibiting the growth of melanoma cells. The results showed that 20% turmeric rhizome extract cream was the formulation that gave the best IC50 value of 524.42 ± 5.2 g/mL.